Big data and ICT solutions in the European Union and in China: A comparative analysis of policies in personalized medicine. (October 2022) - Causio, Francesco Andrea; Hoxhaj, Ilda; Beccia, Flavia; Marcantonio, Marzia di; Strohäker, Timo; Cadeddu, Chiara; Ricciardi, Walter; Boccia, Stefania
Introduction: Several countries are either planning or implementing national strategies for the development and integration of Personalized Medicine (PM) into their healthcare systems. Personalized Medicine is an undisputed priority of the European Commission (EC), which has funded the project "Integrating China into the International Consortium for Personalized Medicine" (IC2PerMed), in order to ensure a common basis for Sino-European collaborations. By mapping the current PM landscape in the European Union (EU) and in China, IC2PerMed aims to provide key solutions toward a synergistic and coordinated approach in the field of PM. Methods: An extensive desk research was conducted, aimed at identifying documents on PM-related policies, programs, and action plans in the EU and in China, published up to November 2020. The search was conducted by exploring scientific and gray literature, and official institutional repositories. A descriptive summary condensed the information retrieved for both. Results: Since 2013, the year of publication of the first PM policy by the EC "Use of omics technologies in PM development, " several documents have been published. PM is a key element of the policy agenda also in China, which in 2016 integrated PM into the 13th National Five-Year Plan, followed by the publication of several policies on technology infrastructure and big data. Both in the EU and China, especially in recent years, these policies addressed in detail the issues of big data, data interoperability and exchange, while defining the standards of information and communication infrastructures. Conclusions: In order to allow optimal collaboration, it is essential to understand similarities and differences between the respective policy strategies, with particular attention to data management and adopted infrastructures. The results of this project may enable the development of joint Sino-European research and innovation initiatives, promoting developments in the field of PM.